2004
DOI: 10.1002/hep.20091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytomorphological detection of circulating tumor cells in patients with liver cancer

Abstract: The clinical impact of circulating tumor cell (CTC) detection is controversial, mainly due to drawbacks of molecular approaches applied to this field. We sought to determine if the specific identification and counting of circulating tumor cells by cytomorphologic analysis has clinical usefulness. Peripheral blood (6 mL), treated using isolation by size of epithelial tumor cells, was obtained from 44 patients with primary liver cancer (PLC) and without metastases, 30 patients with chronic active hepatitis, 39 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
172
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 17 publications
1
172
0
3
Order By: Relevance
“…However, recent reports suggest that detection of CTM, which MCF-7 aggregates may mimic, is important because metastasis are being emphasized via CTM, rather than via a single CTC. Thus, a CTC at the center of a microembolus may play a metastatic role (2,31). According to this idea, the outer cells may undergo Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports suggest that detection of CTM, which MCF-7 aggregates may mimic, is important because metastasis are being emphasized via CTM, rather than via a single CTC. Thus, a CTC at the center of a microembolus may play a metastatic role (2,31). According to this idea, the outer cells may undergo Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we further optimized the size-based microfluidic chip that had previously reported by our group [16]. The principle behind this microfluidic device is that most cancer cells are larger size and less deformability than blood cells make them less likely to traverse through the channels while most blood cells pass through [23]. The size-based microfluidic device presented here thus encompasses major advances over the previous methods.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, a three-step sequential process was developed in an attempt to enrich and isolate CTCs from a large blood volume based upon their physical characteristics by (1) leukapheresis and (2) elutriation, and immunologically by (3) FACS. Current enrichment techniques are restricted by the low amount of blood that can be processed requiring sensitive detection methods to identify only a few CTCs within a large background of leukocytes (12,18,(42)(43)(44)(45). The use of leukapheresis to collect CTCs from cancer patients has the propensity to limit CTC escape and increase the amount of CTCs isolated by subsequent methods.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs have generally been enriched based upon their physical character by their density using gradient centrifugation (9,14,15) and by their large size using micro-filtration (16)(17)(18)(19), or immunologically using antibodies targeting such as the epithelial cell adhesion molecule (EpCAM) that are immobilized on substrates including microfluidic chambers and magnetic beads for CTC adsorption (10,12,20). The enrichment of CTCs using gradient centrifugation and/ or immunomagnetic bead adsorption revealed a CTC incidence rate of 20% in ovarian cancer patients at primary diagnosis.…”
mentioning
confidence: 99%